V1–V2–V3–V4 T wave inversion: left or right ventricle?. (9th October 2013) - Mirijello, Antonio; Pola, Roberto; Saviano, Luisa; Landolfi, Raffaele
Abstract : An 84-year-old woman, affected by Alzheimer's disease, presented to the emergency department with intense dyspnoea. Since ECG was showing T wave inversion in anterior leads and troponin-T was high, the patient was admitted to our unit with a diagnosis of anterior non-ST elevation myocardial infarction. However, the patient's medical history and a further review of the ECG led us to suspect a pulmonary embolism (PE) as a possible differential clinical diagnosis. We tested this alternative hypothesis: echocardiography as well as contrast-enhanced CT scan confirmed the diagnosis of PE. We describe these misleading ECG findings together with a brief discussion of electrocardiographical changes in pulmonary embolism.